SOCIAL ACTIVITY OF WOMEN IN SOCIETY - Hamidullaevna, Islamova Dildora; Akhmedovna, Akhrorova Sevar; Halilovna, 3Mamadieva Nilufar (International Journal of Psychosocial Rehabilitation, 2020)
Disclosure of the essence, content and mechanism of social activity, the study of the state and dynamics of changes in the status of women, their social and political behavior in the context of society reform, trends, problems and prospects for the development of women’s social activity and, on this basis, the development of practical recommendations for motivating Vietnamese social activity women. Interest in the study of the problems of women's social activity is caused by the increasing role of man in modern conditions of reforming as the subject of activity responsible for the ongoing changes. Their success is impossible without such components of the human factor as goal-setting, orientation of the broad masses. Any transformation is the result of social, political, labor activity, during which a person is not only the main goal of social development, but also an enduring value. All this is unthinkable without taking into account the role of women, who make up almost half of the population. Their social status and role are an active factor in social life.